Gambaran Tingkat Pengetahuan Ibu Tentang Pemberian Imunisasi Lanjutan Pada Balita Usia 18 Sampai 24 Bulan di Desa Lempeni Kecamatan Tempeh Kabupaten Lumajang - Kurniawati, Dinik; Farianingsih, Farianingsih; Rohmatin, Homsiatur (NHM PRESS, 2023)
Follow-up immunization is a repeat of basic immunization to maintain the level of immunity and to extend the protection period for children who have received basic immunization by giving 1 dose of DPT-HB-HiB at the age of 18 months and 1 dose of measles/MR at the age of 24 months. Optimal protection from the provision of further immunization is only obtained if the child has received complete basic immunization (RI Ministry of Health, 2018). Immunization coverage is closely related to the knowledge of mothers and families about giving immunizations to get immunizations because the higher the knowledge of parents about immunization, the higher the immunization coverage rate (Eva Supriatin, 2015). This study aims to determine and analyze the level of knowledge of mothers about advanced immunization for toddlers aged 18 to 24 months in Lempeni Village, Tempeh District, Lumajang Regency, which was carried out in July-August 2022. The type of research carried out was all mothers who had toddlers aged 18 to 24 months, sampling by total sampling so that the sample obtained is 40 respondents. Data collection includes coding, editing, and tabulating, then the data is analyzed manually using formulas. The results showed that of the 40 respondents, most of them had a sufficient level of knowledge about advanced immunization, namely from 40 respondents who had a sufficient level of knowledge as many as 19 people (47.5%), a good level of knowledge as many as 14 people (35%), and a good level of knowledge. less than 7 people (17.5%).